National Network of Fusion Centers : effectiveness, capabilities & performance - Lincoln, Nancy C.; Seegmiller, Janet Burton (Defense, security and strategy series., 2014)
In the aftermath of the information sharing failures leading to the September 11, 2001 terrorist attacks that killed nearly 3,000 people in New York City, at the Pentagon, and in a Pennsylvania field, states and localities across the United States established what are known today as State and Major Urban Area Fusion Centers. Collectively known as the National Network of Fusion Centers, many of these (now numbering 78) fusion centers are still in their infancy. The Homeland has been attacked five times since 2001: the Little Rock Recruiting Station shooting (2009); the Fort Hood shooting (2009).